(untitled) (Swiss Medical Weekly, 2021)
Occupational disease lists (ODLs) are essential legal mechanisms for recognising pathologies related to exposure to occupational hazards. In 2017, Switzerland revised its ODL and solicited stakeholders to review the ODL proposal. This revision represented an important and rare event, and was an opportunity to assess the legal status and role of Swiss ODL. In this research, we examined the structure and content of this revised Swiss list, by comparing it to other official recommendations and ODLs, including those of the International Labour Organization (ILO) and the European Commission (EC). In addition, we assessed the effectiveness of the Swiss ODL from the occupational and public health perspectives, in considering the process of reporting and recognition of occupational diseases as a measure for protecting the health of workers. Although the Swiss ODL appears to be in accordance with the ILO and EC recommendations, its role as a legal mechanism of workers’ protection is not optimal. Its effectiveness is limited by the conditions for recognising a disease as occupational, which are determined by Swiss federal law and are stricter than in other countries. The overall burden of occupational diseases has a significant economic, social and moral impact on working populations, their families and society as a whole. As such, more transparency with respect to the ODL revision and conditions for recognising occupational disease and to the data on recognised and reported cases, along with continuous education of physicians are required to enhance the effectiveness of the Swiss system of recognition and reporting of occupational diseases and protection of Swiss workers.